2011
DOI: 10.1016/j.annemergmed.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions Targeting Frequent Users of Emergency Departments: A Systematic Review

Abstract: Interventions targeting frequent users may reduce ED use. Case management, the most frequently described intervention, reduced ED costs and seemed to improve social and clinical outcomes. It appears to be beneficial to patients and justifiable for hospitals to implement case management for frequent users in the framework of a clear and consensual definition of frequent users and standardized outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
316
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(328 citation statements)
references
References 57 publications
6
316
0
2
Order By: Relevance
“…regression to the mean), even without intervention. 7,19 Finally, the Hawthorne effect-that people have a tendency to change their behavior when under observation-may have influenced ED use among these participants. In the Reinius study, 13 control participants were passively observed in a Zelen's design, adopted in part to avoid a Hawthorne effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…regression to the mean), even without intervention. 7,19 Finally, the Hawthorne effect-that people have a tendency to change their behavior when under observation-may have influenced ED use among these participants. In the Reinius study, 13 control participants were passively observed in a Zelen's design, adopted in part to avoid a Hawthorne effect.…”
Section: Discussionmentioning
confidence: 99%
“…Based on results from a systematic review of the literature, 7 the sample size estimate was calculated to detect an average difference of two ED visits annually between the two groups (i.e. four fewer intervention group visits compared to two fewer control group visits, with an anticipated standard deviation of four in both groups).…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…3 Numerous interventions have been implemented over the years to reduce discretionary ED utilization rates. 4 Recently, efforts to reduce ED utilization have included redesigning the primary care delivery system (eg, implementation of a patient-centered medical home) 5,6 and introducing financial incentives to primary care physicians (PCPs). [7][8][9] The rationale for both the approaches is that primary care can exert substantial influence on patterns of ED utilization and that altering the current model of primary care delivery can affect ED use by patients.…”
Section: Introductionmentioning
confidence: 99%
“…8 Many reviews have documented the positive impacts of case management among frequent users of health care services. Althaus et al 9 concluded that case management decreased emergency department use and costs, and improved clinical and social outcomes. Reviews by Kumar and Klein 6 and Soril et al 5 also reported that the majority of evidence pointed to the benefits of case management interventions for frequent users.…”
Section: Introductionmentioning
confidence: 99%